A pan-Canadian study of registered dietitians' perceptions and experiences of interprofessional collaboration. Issue 3 (4th May 2022) - Asher, Kathryn E.; Doucet, Shelley; Luke, Alison
ABSTRACT: Little is known about Canadian dietitians' perceptions and experiences of interprofessional collaboration. To address this knowledge gap, a cross-sectional online survey was administered to registered dietitians in Canada. Quantitative data was analyzed in SPSS using descriptive and inferential statistics, while thematic analysis was used for open-text responses. A total of N = 469 registered dietitians representing 10 provinces participated in the study. Results showed a significant difference ( p < .001) between the frequency with which dietitians collaborated with other health and social care providers and their desired frequency, with 61.0% indicating they wanted more frequent collaboration. A majority of dietitians (59.2%) had negative views of interprofessional interactions. Nearly all respondents felt there is a need to raise better awareness about the dietetic profession (95.4%) and that dietitians are underutilized in the world of healthcare (92.5%). On three measures, a majority of participants (ranging from 65.6% to 81.5%) reported that their dietetic training helped equip them for interprofessional collaboration. Insufficient time/availability was the obstacle to interprofessional collaboration cited most frequently by dietitians. Results suggest that interprofessional collaboration is an area in need of attention in the Canadian dietetic profession, as well as with health and social care providers who work with dietitians. The study's findings point to potential areas for improvement.